Estudio de factibilidad para la creación de una estación de servicios vía al vergel cantón Valencia, año 2014 - Saltos Olmedo, Gabriela Roció (2015)
All companies are of great importance for the country and thanks to their financial stability has been developed every day our Ecuador, this makes companies grow and organize themselves to meet the objectives to better business performance. Financial institutions provide loans to various companies including depreciation and are deferred amount as established, this makes the economy and jobs increases. Investments have big decision at the time of working capital should be performed cost analysis merchandise, merchandise revenue, the raw material to be implemented for this investment, fixed assets, income statements are most important for the investment company, earning $ 726,973.26 USD NPV and IRR $ 102.40 with benefit cost $ 1.09 for the first year of investment. In the parroquia Hope there is a service station which must refuel vehicles generating a high percentage of great economic and social demand for its high level of consumption in the city, but around the city there are many farmers they need fuel supply which are difficult for their harvest machinery, vehicles when leaving and arriving to the station serves well to keep wasting time at work….